Making an Online Dictionary of New Zealand Sign Language - McKee, Rachel Locker; McKee, David (Lexikos, 2013)
The Online Dictionary of New Zealand Sign Language (ODNZSL), launched in 2011, is an example of a contemporary sign language dictionary that leverages the 21st century advantages of a digital medium and an existing body of descriptive research on the language, including a small electronic corpus of New Zealand Sign Language. Innovations in recent online dictionaries of other signed languages informed development of this bilingual, bi-directional, multimedia dictionary. Video content and search capacities in an online medium are a huge advance in more directly representing a signed lexicon and enabling users to access content in versatile ways, yet do not resolve all of the theoretical challenges that face sign language dictionary makers. Considerations in the editing and production of the ODNZSL are discussed in this article, including issues of determining lexemes and word class in a polysynthetic language, deriving usage examples from a small corpus, and dealing with sociolinguistic variation in the selection and performance of content. Keywords: sign language lexicography, online dictionaries, multimedia dictionaries, bilingual dictionaries, learner dictionaries, new zealand sign language, video content, sign language corpus, polysynthetic morphology, polysemy, sociolinguistic variation, sign language linguistics, user profile